ChemInform Abstract: Aza‐Wacker‐Type Reaction Between Electron‐Deficient Olefins and N‐Alkylsulfonamides. Issue 29 (July 2015) - Hu, Huayou; Tian, Jiaxin; Liu, Yun; Liu, Yong; Shi, Fei; Wang, Xiang; Kan, Yuhe; Wang, Chao
Abstract A scalable protocol for the oxidative amination of electron‐deficient olefins in presence of methanesulfonic acid is presented.